Optimizing Tuberculosis Treatment through Health Management: Addressing Environmental and Socioeconomic Determinants - Siska Hidayani (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Tuberculosis remains a major public health challenge, with treatment outcomes influenced by the complex interplay of environmental, socioeconomic, and health system factors. This study aims to analyze the key determinants affecting tuberculosis treatment success from a health management perspective, focusing on how contextual conditions shape patient adherence and program effectiveness. A systematic literature-based approach was employed, reviewing empirical and review articles published in peer-reviewed journals over the past decade. The analysis centered on three main aspects: environmental determinants, socioeconomic conditions, and healthcare system factors related to tuberculosis treatment outcomes. Findings indicate that poor housing conditions, air pollution, and low environmental quality increase the risk of adverse treatment outcomes. Moreover, low socioeconomic status, financial constraints, and social stigma significantly undermine patient adherence, while barriers to healthcare access, including long travel distances, inadequate infrastructure, and limited human resource capacity, exacerbate treatment failure and patient loss to follow-up. These results highlight the importance of integrated tuberculosis control strategies that extend beyond clinical interventions, encompassing strengthened service delivery, enhanced patient support mechanisms, and the integration of socioeconomic and environmental considerations. A multisectoral, patient-centered approach is essential to improve tuberculosis treatment outcomes and reduce the overall disease burden.